Traditional Knowledge Management Study of ’Bastralaya’: Investigation of Proposed ’Narrative Inquiry’ Method - Kar, Surjit Kumar; Satpathy, Biswajit (Prabandhan: Indian Journal of Management, 2012)
This paper mainly focuses on the study of a rural handloom cooperative enterprise within a traditional community culture in the hinterlands of an agrarian state. The growing importance of community driven enterprise on socio-economic facets of its people is the major importance and motivation for such a study. The study constitutes a premise on certain statement of problems for the research. Traditional Knowledge Management (TKM) is an area of subjective study with clear research objectives and purposes. Thus, a considerable theoretical framework is built for a thorough methodological investigation. The paper highlights the design, approach, limitations, and delimitations of the study. This paper is basically a precursor to the subsequently undertaken extensive primary field work and research in the concerned area in early part of the year 2010. Qualitative method such as Narrative Inquiry and its applicability for the proposed study is investigated and established in this paper. Such qualitative methods need utmost willingness & availability of the subjects under study. The accrued benefits of such unique studies can be in the form of contribution to the existing domain of literature on traditional knowledge as an integral part of rural and regional economy of the country. It can also enrich the qualitative research paradigm for the researchers having a similar interest.